Environmental disclosure and public ownership: Further evidence - Sururi, Rais Ahmad; Ismail, Mutia (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Due to the considerable influence that company operations have on the environment, there is a growing demand for firms to provide transparent information about their environmental impact. The purpose of this study is to determine the effect of profitability, company size, leverage and public ownership on environmental disclosure in basic industrial and chemical sector manufacturing companies listed on the IDX for the 2018-2021 period. The study had a population of 69 companies. The sampling technique used is purposive sampling so that 20 companies are obtained to be studied. The type of data used is secondary data and the data analysis techniques used are multiple linear regression test. The results indicate that public ownership has a positive influence on environmental disclosure. Meanwhile, profitability, size, and leverage do not exhibit any significant impact on environmental disclosure. This research contributes to the environmental disclosure literature by emphasizing the necessity of considering public ownership asa crucial factor.